The effects of some antibiotics and lipopolysaccharide on oxidative burst and phagocytosis of neutrophils - Böhmer, Reinhard Hansi (Division of Medical Microbiology, 2017)
The determination of phagocytosis (P) and oxidative burst (OB) in unfractionated blood is a rapid and sensitive flow cytometric method for quantifying neutrophil activation, and was modified for single laser systems by using propidium iodide labeled Staphylococcus aureus (S.aureus) as a quantitative measure of phagocytosis and simultaneously the green fluorescence of oxidized 2'7' dichlorofluorescein diacetate was used to measure oxidative burst. Propidium-iodide labels dead organisms by intercalation with the DNA of the dead organism. This assay was characterized with respect to the stimulatory activity of bacterial lipopolysaccharide (LPS) on OB and P and to determine the effects of lipopolysaccharide and different antibiotics on oxidative burst and phagocytosis by polymorphonuclear leukocytes (PMNL) using a FACS 440 flow cytometer. Blood from healthy donors was pre-incubated with log doses of bacterial LPS (0.1 ng/ml - 1000 ng/ml) or sterile pyrogen-free saline at 37 °c from 0-120 minutes. LPS increased both phagocytosis and oxidative burst in a dose-dependent manner (up to 62 and 121 percent respectively) at all time points tested, and this effect on P and OB could be detected even with no pre- incubation. This LPS - induced phagocytic activity could be blocked by the addition of polymyxin B (10 μg/ml) during preincubation. The priming effect of LPS was maximal at 45 minutes. P and OB were inhibited by pre-incubation with EDTA at doses greater than 1000 μg/ml (60 and 80 percent inhibition) respectively. These observations are consistent with the exquisite sensitivity of the neutrophil to endotoxin. Blood from healthy subjects was subjected to different concentrations of antibiotics, or sterile pyrogenfree saline at 37 °c from O to 120 minutes. The antibiotics used were the following: Ceftriaxone, ciprofloxacin, clindamycin, doxycycline, enoxacin, imipenem, norfloxacin, pefloxacin, teicoplanin, tetracycline and vancomycin. Blood from healthy subjects was exposed to concentrations of the above antibiotics ranging from 0.1 to 200 μg/ml for 60 minutes. EDTA and bacterial LPS used as system controls demonstrated dose-dependent inhibition and increase respectively. Doxycycline showed inhibition of both parameters, while pefloxacin enhanced and tetracycline inhibited oxidative burst. The remaining antibiotics showed no doserelated modulation of either oxidative burst or phagocytosis. The method described provides an environment that mimics physiological conditions; is a rapid and sensitive assay not requiring separation of white cells; and simultaneously measures two neutrophil functions. It can evaluate neutrophil response to immunomodulatory and chemotherapeutic agents in a physiological milieu. The necessity of using pyrogen - free reagents in any study of neutrophil function is re-emphasized.